Avaliação do efeito de lactobacillus casei DN114001 no tratamento de mucosite induzida por 5-FU - Indianara Machado (2018)
The gastrointestinal mucositis is one of the major and most serious consequences of antineoplastic therapy, leading the patient to debilitation or even death, often requiring the interruption of chemotherapy. Despite the frequency and clinical importance, there is still no effective treatment against mucositis. Even with advances in research, its pathobiology has not yet been fully elucidated; however, it is known that the indigenous microbiota is involved in its development. One aspect of mucositis caused by, such as 5-fluorouracil (5-FU), is the change in the intestinal microbiota, and some studies show that the altered microbiota leads to the worsening of the disease. Thus, it's clear the importance of probiotics, which may serve as adjuvant therapy for mucositis, by modulating the microbiota and the immune response. The aim of this study was to evaluate whether administration of the probiotic Lactobacillus casei DN114001, would protect mice against 5-FU induced mucositis. We investigated the treatment with the bacteria, administered in a preventive / curative way, evaluating: weight loss and food consumption, intestinal permeability, presence of neutrophil and eosinophil infiltrates and sIgA levels, as well as pathological parameters at the histological level and the amount of enterobacteria. The results showed that, at the histological level, the bacteria provided a slight protection to the intestinal mucosa, presenting a slight decrease in intestinal permeability, and the in level of enterobacteria; however these results were not statistically different. The bacteria did not prevent the decrease of sIgA levels and goblet cell counts, nor the shortening of the intestinal villi. Likewise, it did not prevent an increase in inflammatory cell infiltrates, nor a decrease in food consumption, demonstrating to have a very discrete effect on some aspects of mucositis. It was therefore concluded, that L. casei DN114001 does not protect the animals against 5-FU induced mucositis.